2001
DOI: 10.1111/j.1095-8649.2001.tb00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of bream between the main channel and floodplain lakes along the lower River Rhine during the connection phase

Abstract: Mature bream (>30 cm L F ) dominated the fish communities in floodplain lakes along the lower River Rhine in The Netherlands, in terms of biomass, in all lakes at all times. In some lakes bream made up 99% of the total fish biomass. While immature, medium-sized bream (10-30 cm) and white bream and roach were abundant in the main channel of the river, these species were almost absent from the floodplain lakes. Inundation of the floodplains did not lead to spatial homogenization of species and length distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 21 publications
3
13
2
Order By: Relevance
“…Chub is usually observed to migrate mainly at night (Lucas 2000), with peak between 22.00 and 05.00 h (Prignon et al 1998), behaviour we observed in movements out of the backwater. In contrast to reports from the lower Morava (Copp & Jurajda 1999) and elsewhere, e.g., for common bream (Molls 1999;Grift et al 2001), we observed no obvious size-dependent migratory activity of the species.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Chub is usually observed to migrate mainly at night (Lucas 2000), with peak between 22.00 and 05.00 h (Prignon et al 1998), behaviour we observed in movements out of the backwater. In contrast to reports from the lower Morava (Copp & Jurajda 1999) and elsewhere, e.g., for common bream (Molls 1999;Grift et al 2001), we observed no obvious size-dependent migratory activity of the species.…”
Section: Discussioncontrasting
confidence: 99%
“…Intensive two-way movements of fish were observed in the short 'r-b' connection between the main channel of the River Morava and the Kurfu¨rst backwater, mainly during spring high water levels. This coincided with the spawning periods of the main species observed, and in general resembles the lateral spawning migration reported elsewhere (Welcomme 1985;Molls 1999;Grift et al 2001). The considerable decrease in the water level between 16 and 26 May coincided with reduced fish movements of all fish species through the 'r-b' connection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, many species exhibit lateral migration behaviour between main river channels, side channels and floodplain waters, especially in lowland rivers (Aarts & Nienhuis 2003). The status of these species gives an indication of the morphological condition of the river channel and its connectivity with the active floodplain (Welcomme 1979;Grift, Buijse, Breteler, Van Densen, Machiels & Backx 2001;Aarts, Van Den Brink & Nienhuis 2004). Therefore, any scheme to classify migration should reflect the overall connectivity of a river system and include scope for classification of lateral migration requirements of floodplain species.…”
Section: Life-history Strategies: Migration Guildsmentioning
confidence: 99%